The spatial distribution of wave overtopping volumes over a composite smooth impermeable seawall with an impermeable berm - Shudi Dong; Md Salauddin; Qin Jiang; Yongming Zheng; Yanming Yu; Siyuan Hong; Ziwei Li (Ocean Engineering, 2026)

Association between agricultural training and the adoption of sustainable soil management practices in coastal Bangladesh - Md. Salauddin Palash; Md Mahfuzul Hasan; Syeda Subrina Sultana; Muhammed Ali Hossain; Ahmed Khairul Hasan (Journal of Coastal Conservation, 2026)

Smallholder participation in premium rice markets in Bangladesh: A structural equation model for understanding production and marketing decisions - Md. Tanvir Ahmed; Mohammad Saidur Rahman; Matty Demont; Islam Abu Hayat Md Saiful Islam; Md. Salauddin Palash; Ishika Gupta; Prakashan Chellattan Veettil (Agricultural Systems, 2026)

Coastal protection services provided by nature-based solutions: artificial and natural reefs - Mirajul Hossain; Deborah Villarroel-Lamb; Md Salauddin (Frontiers in Marine Science, 2026)
Coastal protection has become a critical global priority due to escalating coastal erosion associated with sea-level rise and increasing storm surges. Conventional hard-engineering structures, while effective in reducing wave energy, often result in substantial degradation of marine ecosystems, raising concerns about long-term sustainability and ecological resilience. As a response, nature-based solutions (NBS), including oyster or coral reef restoration as part of living shoreline systems, have gained increasing attention for their potential to simultaneously provide coastal defense and enhance marine habitat quality. In addition to that submerged artificial reefs or breakwaters can be characterized as ecologically improved gray infrastructure or hybrid coastal defense systems that can promote secondary ecological functions by offering substrate for habitat development and species colonization, functioning similarly to nature-based solutions (NBS). Numerous investigations on both naturally occurring reefs and artificial reefs, conducted through laboratory experiments, numerical modeling, and field implementations assess the engineering performance of coastal protection services. This study aims to review current investigations systematically on naturally occurring reefs (oysters or coral) or submerged artificial reefs, evaluating their principal functions, limitations, and methodological approaches to attenuate wave energy while critically synthesizing the research approaches with corresponding findings to highlight the advancements in coastal protection services. The outcomes presented herein aim to guide coastal managers, engineers, researchers, and policymakers towards the development and implementation of sustainable, ecosystem-based coastal protection strategies that integrate both engineering efficacy and environmental enhancement.

Projected Changes in Wind Characteristics over Ireland Based on the CMIP6 Models Under the SSP Scenarios - Fulya Islek; Md Salauddin (Journal of Marine Science and Engineering, 2026)
This study presents a comprehensive assessment of historical and projected variability in the wind climate over Ireland and its adjacent marine regions, including the North Atlantic Ocean, Irish Sea, and Celtic Sea. First, the long-term wind characteristics are examined using the ERA5 reanalysis dataset for the historical period (1979–2008), followed by an evaluation of five CMIP6 Global Climate Models (GCMs) to determine their performance in representing regional wind climatology. Based on spatial validation and relative bias analyses, the most suitable model is selected to investigate future wind changes under the SSP2-4.5 and 5-8.5 scenarios. The CMIP6 historical data is also compared locally at seven measurement stations. Two future projections are considered for the near-term (2031–2060) and mid-term (2071–2100), focusing on inter- and intra-annual variability and extreme wind behaviour. The results indicate an overall decrease in mean wind speed across the study area, with more pronounced reductions under SSP5-8.5 and during the mid-term period. In terms of seasonality, reductions are more pronounced during winter and summer than in the transitional seasons. According to the extreme value analysis based on the generalised extreme value distribution, general declines in extreme values are detected at selected critical locations, especially at wind speeds with large return periods.

Examining the nexus between climate change perceptions and good agricultural practices: a focus on coastal regions of Bangladesh - Md. Salauddin Palash; Muhammed Ali Hossain; Md. Mahfuzul Hasan; Ahmed Khairul Hasan; Syeda Subrina Sultana (Mitigation and Adaptation Strategies for Global Change, 2025)

Shoreline dynamics in response to sea-level changes on the eastern coast of Bangladesh - Md.Mehedi Hasan Saddam; Khandaker Tanvir Hossain; Porni Mollick; Md. Salauddin; Sanjoy Roy; Arif Uddin Ahmad; Ratan Chandra Bhowmick; Md.Ashikul Islam Rony (Environmental Monitoring and Assessment, 2025)
The eastern coast of Bangladesh has undergone significant geomorphic changes since 1990, with the shoreline predominantly prograding towards the Bay of Bengal. Analysis indicates that the northeastern (Mirsarai- Banshkhali) coast experienced seaward progradation, with a maximum progradation of 3.87 km and an average rate of 0.13 km/year over the past 30 years. Conversely, the south-eastern coast (Cox’s Bazar toward Teknaf) exhibited landward movement due to erosion, with a maximum retreat of 2.9 km and an average rate of 0.096 km/year. These changes were quantified using remote sensing and the Digital Shoreline Analysis System (DSAS), an ArcGIS extension, to calculate Net Shoreline Movement (NSM) and Linear Regression Rate (LRR) with 95% confidence intervals. Shorelines were manually digitized from Landsat images at a fixed scale of 1:2500 to ensure precision. Mean Sea Level (MSL) data from two tidal stations revealed fluctuating trends over time. At Enayethat station, a weak uphill positive correlation was found between sea-level rise and shoreline erosion ( R 2 = 0.06), whereas at Lemshikhali station, the MSL decreased between 1990 and 2019, and a moderate uphill positive correlation ( R 2 = 0.43) with shoreline erosion was observed. The findings indicate that accretion along the eastern shoreline surpasses erosion. Sedimentation in the estuary and the stabilizing influence of eastern hills contribute to a long-term trend of shoreline stability and seaward expansion. Importantly, no direct relationship was identified between sea-level rise and coastal erosion, highlighting the dominance of localized geomorphic and sedimentary processes in shaping shoreline dynamics. These results could reflect similar patterns of change in other tropical shorelines worldwide.

Distinct amino acid substitutions in the EEV glycoprotein and DNA-dependent RNA polymerase of lumpy skin disease virus identified in wetland areas of Bangladesh - Moslema Jahan Mou; S.M. Nazmul Hasan; Anandha Mozumder; Marjana Akter; Riyan Al Islam Reshad; Roni Mia; Md. Salauddin; M. Shaminur Rahman; Md. Mahmudul Alam; Sharmin Akter; Sukumar Saha; Tofazzal Islam; et al. (Research in Veterinary Science, 2025)

Whole-Genome Analysis of Multidrug-Resistant Klebsiella pneumoniae Kp04 Reveals Distinctive Antimicrobial and Arsenic-Resistance Genomic Features: A Case Study from Bangladesh - Md. Javed Foysal; Farhana Momtaz; A. M. Masudul Azad Chowdhury; Afroza Akter Tanni; Asma Salauddin; Md. Zahid Hasan; Sohana Akter Mina; Nahid Sultana; Sanjoy Kanti Biswas; Kamrul Islam; Alfred Tay; Adnan Mannan (Current Microbiology, 2025)

Source identification of heavy metals and metalloids in soil using open-source Tellus database and their impact on ecology and human health - Rayhan Uddin; Philip K. Hopke; Jan Van Impe; Srikanta Sannigrahi; Md Salauddin; Enda Cummins; Rajat Nag (Science of The Total Environment, 2024)

WGS-based screening of the co-chaperone protein DjlA-induced curved DNA binding protein A (CbpA) from a new multidrug-resistant zoonotic mastitis-causing Klebsiella pneumoniae strain: a novel molecular target of selective flavonoids - Mohammad Habibur Rahman; Salauddin Al Azad; Mohammad Fahim Uddin; Maisha Farzana; Iffat Ara Sharmeen; Kaifi Sultana Kabbo; Anika Jabin; Ashfaque Rahman; Farhan Jamil; Sanjida Ahmed Srishti; Fahmida Haque Riya; Towhid Khan; et al. (Molecular Diversity, 2024)

Trend of heat waves in Dhaka Metropolitan City and its impact on livelihood and health of exposed people - Md Yachin Islam; Md. Mohiuddin; Khandaker Tanvir Hossain; Md. Salauddin; Samiya Farin (Arabian Journal of Geosciences, 2024)

Oncoinformatic screening of the gene clusters involved in the HER2-positive breast cancer formation along with the in silico pharmacodynamic profiling of selective long-chain omega-3 fatty acids as the metastatic antagonists - A K M Helal Morshed; Salauddin Al Azad; Md. Abdur Rashid Mia; Mohammad Fahim Uddin; Tanzila Ismail Ema; Rukaiya Binte Yeasin; Sanjida Ahmed Srishti; Pallab Sarker; Rubaita Younus Aurthi; Farhan Jamil; Nure Sharaf Nower Samia; Partha Biswas; et al. (Molecular Diversity, 2023)

Assessing the shoreline dynamics of Moheskhali Island in Bangladesh by integrating GIS techniques and sea-level data - Md. Mehedi Hasan Saddam; Khandaker Tanvir Hossain; Ratan Chandra Bhowmick; Md. Salauddin; Tarak Aziz (Regional Studies in Marine Science, 2023)

Factors influencing the financial and relational governance in Bangladesh's inland fishing industry: An empirical study - Md. Masudul Haque Prodhan; Md. Salauddin Palash; Md. Akhtaruzzaman Khan (Marine Policy, 2023)

Association between TCF7L2 polymorphism and type 2 diabetes mellitus susceptibility: a case–control study among the Bangladeshi population - Asma Salauddin; Kallyan Chakma; Md. Mahbub Hasan; Farhana Akter; Nowshad Asgar Chowdhury; Sumon Rahman Chowdhury; Adnan Mannan (Molecular Biology Reports, 2023)

Appraisal of stormwater-induced runoff quality influenced by site-specific land use patterns in the south-eastern region of Bangladesh - Sudip Kumar Pal; Md. Mehedi Hassan Masum; Md. Salauddin; Md. Arif Hossen; Israt Jahan Ruva; Afsana Alam Akhie (Environmental Science and Pollution Research, 2022)

Eco-Engineering of Seawalls—An Opportunity for Enhanced Climate Resilience From Increased Topographic Complexity - Md Salauddin; John J. O’Sullivan; Soroush Abolfathi; Jonathan M. Pearson (Frontiers in Marine Science, 2021)
In the context of “green” approaches to coastal engineering, the term “eco-engineering” has emerged in recent years to describe the incorporation of ecological concepts (including artificially water-filled depressions and surface textured tiles on seawalls and drilled holes in sea structures) into the conventional design process for marine infrastructures. Limited studies have evaluated the potential increase in wave energy dissipation resulting from the increased hydraulic roughness of ecologically modified sea defences which could reduce wave overtopping and consequent coastal flood risks, while increasing biodiversity. This paper presents results of small-scale laboratory investigations of wave overtopping on artificially roughened seawalls. Impulsive and non-impulsive wave conditions with two deep-water wave steepness values (=0.015 and 0.06) are evaluated to simulate both swell and storm conditions in a two-dimensional wave flume with an impermeable 1:20 foreshore slope. Measurements from a plain vertical seawall are taken as the reference case. The seawall was subsequently modified to include 10 further test configurations where hydraulic effects, reflective of “eco-engineering” interventions, were simulated by progressively increasing seawall roughness with surface protrusions across three length scales and three surface densities. Measurements at the plain vertical seawall compared favorably to empirical predictions from the EurOtop II Design Manual and served as a validation of the experimental approach. Results from physical model experiments showed that increasing the length and/or density of surface protrusions reduced overtopping on seawalls. Benchmarking of test results from experiments with modified seawalls to reference conditions showed that the mean overtopping rate was reduced by up to 100% (test case where protrusion density and length were maximum) under impulsive wave conditions. Results of this study highlight the potential for eco-engineering interventions on seawalls to mitigate extreme wave overtopping hazards by dissipating additional wave energy through increased surface roughness on the structure.

Assessment of biogas generation potential from slaughterhouse wastes in Dhaka city, Bangladesh - Sayedus Salehin; Syed Shaheer Uddin Ahmed; Md. Ehasanul Hoque; Md. Salauddin Mrigdad; S. M. Ashef Hussain; S. M. Tahsin Intisar (Waste Disposal & Sustainable Energy, 2021)